On the Existence of Critical Clique-Helly Graphs - Alcón, Liliana Graciela (2017)
A graph is clique-Helly if any family of mutually intersecting cliques has non-empty intersection. Dourado, Protti and Szwarcfiter conjectured that every clique-Helly graph contains a vertex whose removal maintains it a clique-Helly graph. We will present a counterexample to this conjecture.